Delineation of Catchment Boundary for Flood Prone Area: A Case Study of Pekan Town Area - Noor Asiah, Mohamad; Ow, Yu Zen; Idrus, Ahmad (2017)
Pekan town is located in the downstream of Pahang River Basin. It is frequently hit by flood. The most recent major flood in Pekan town occurred from December 2007 to January 2008. Pekan Flood Mitigation Project was implemented by the government with the total protected area of 2,500 ha. Flood Wall were constructed along Pahang Riverside to protect the overflow of the river whereas flood bunds were constructed surrounding the Pekan town to protect the overflow of swamp water from the southern area into the town. Meanwhile internal drain within the protected area is channeled to flow into the South China Sea via the main monsoon drain. The northwest of Pekan town which is located outside the protected area is still hit by flood. The major infrastructures in the northwest of Pekan town consist of hospital, mosque, local industry and residential area. The main causes of the flood in the northwest of Pekan town are due to the overflow of Pahang River and swamp surrounding the area. Flood mitigation measure should be carried out to protect the area. The objective of this research is to delineate the catchment boundary of the flood prone area in the northwest of Pekan Town as part of the flood mitigation study. This research is also aimed to identify the discharge point for the catchment area. Contour lines were extracted from ASTER DEM using ArcGIS and the existing drainage networks were identified based on topographic map. ASTER DEM was used as the best accessible data available for this study. The layout of current drainage networks was verified during the site visit. There were three major drainages in the study area namely Genuk River, West Drain and main drain along the road connecting Pekan town to Muadzam Shah. Based on the layout of current drainage network and contour, it is found that the study area can be divided into two polders (upstream and downstream) with the total area of 1,500 ha. The upstream polder lies on the upstream of Genuk River catchment which are generally flat and swampy. Runoff from the upstream catchment flow into three major drainages mentioned earlier before finally discharged into Pahang River via Genuk River. The downstream catchment lies on the downstream of Genuk River. Runoff from this catchment flow into Genuk River and the main drain before discharged into Pahang River. As noted earlier, the study area in the northwest of Pekan town can be divided into upstream and downstream catchment. Both catchments discharge runoff to Pahang River via Genuk River. Flood mitigation work should be planned considering the two polder areas identified in this study. Further work can be done to extract contour from higher resolution data to improve the result.